DIGITAL TRANSFORMATION OF ISLAMIC BOARDING SCHOOL MANAGEMENT AND ITS IMPLICATIONS FOR IMPROVING EDUCATIONAL SERVICES IN LAMPUNG PROVINCE - Amirudin Amirudin; Ahmad Nur Mizan (QANUN: Journal of Islamic Laws and Studies, 2026)
This study examines the digital transformation in the management of Islamic Boarding Schools (Pondok Pesantren/Ponpes) and its impact on the quality of educational services in three Islamic Boarding Schools in Lampung. The research uses a descriptive qualitative approach with a multi-site case study at Ponpes Terpadu Ushuluddin (South Lampung), Ponpes Al-Hikmah (Bandar Lampung), and Ponpes Nurul Huda (Pringsewu). Data were collected through observation, in-depth interviews with 20 key informants, and documentary studies during the April-October 2024 period. The results show significant variations in digitalization implementation: Ponpes Terpadu Ushuluddin adopted a holistic approach with technology integration in administration, Arabic language learning, and communication; Ponpes Al-Hikmah implemented selective digitalization as a complement to traditional methods; while Ponpes Nurul Huda remains in the early stages with digitalization limited to basic communication. Digitalization has proven to increase administrative efficiency by 40%, expand learning access through digital platforms, and enrich Arabic teaching methods through interactive multimedia. Positive impacts are seen in increased student learning motivation (85%), administrative time efficiency (35%), and management transparency. However, this transformation faces serious challenges including digital infrastructure gaps (especially in rural areas), limitations in managers' technological competence (60% of managers are untrained), cultural dilemmas between modernity and tradition, and budget constraints. This study recommends developing specific digital roadmaps for each pesantren typology, tiered training programs for managers, synergy between local government policies and national programs, and strengthening sustainable digital infrastructure. The research implications provide theoretical contributions to digital transformation models in value-based educational institutions and practical contributions for pesantren managers in designing contextual digital strategies.